Application of Vicarious Liability Principles to Losses from the Use of Artificial Intelligence (AI) from a Civil Law Perspective - Noer Dini Camelia; Win Yuli Wardani; Agustri Purwandi; Alfika Putri Ayuni; Nur Jannatul Aini (IHSA Institute, 2026)
The existence of Artificial Intelligence (AI) as an artificial intelligence system not only provides many benefits but can also cause losses in its use if the AI produces an error that causes harm to others. The occurrence of losses due to the use of AI is certainly related to who is responsible and what form of liability is incurred for the losses caused. The purpose of this study is to determine the form of liability for the use of AI that causes harm based on the principle of vicarious liability or substitute liability. The research method used in this study is normative legal research with a statute approach and a conceptual approach. The results of the study show that, from a civil law perspective, AI cannot be categorized as a legal subject, whereby actions performed by AI are not legal actions that can be held liable. Therefore, the form of liability that can be applied to losses arising from the use of AI is the application of the principle of vicarious liability. In civil law, liability can generally take the form of unlawful acts (Article 1356 of the Civil Code) and vicarious liability (Article 1367 of the Civil Code). The principle of vicarious liability is contained in the provisions of Article 1367 of the Civil Code, which is a form of vicarious liability to another party who is responsible for the actions of another party under their responsibility. Thus, the principle of vicarious liability can be applied in fulfilling the need for a form of liability for losses arising from the use of AI before there are regulations that specifically regulate AI